2017
DOI: 10.3390/ijms18040795
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Speciation of Thorium on Toxic Effects to Green Algae Chlorella pyrenoidosa

Abstract: Thorium (Th) is a natural radioactive element present in the environment and has the potential to be used as a nuclear fuel. Relatively little is known about the influence and toxicity of Th in the environment. In the present study, the toxicity of Th to the green algae Chlorella pyrenoidosa (C. pyrenoidosa) was evaluated by algal growth inhibition, biochemical assays and morphologic observations. In the cultural medium (OECD TG 201), Th(NO3)4 was transformed to amorphous precipitation of Th(OH)4 due to hydrol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Thorium has three alpha-emitting radioisotopes: 228Th (T 1/2 = 1.91 y), 230Th (T 1/2 = 7.54 × 10 4 y), 232 Th (T 1/2 = 1.4 × 10 10 y) [ 99 ], has very low water solubility and strongly adsorb onto organic/inorganic particles, being therefore rather unavailable for biological uptakes [ 100 ]. Adsorbed Th enters the human body through inhalation or ingestion or through skin wounds and excessive exposure can induce cancer of the liver, lungs, pancreas, spleen, bone, and blood [ 101 ]. Th originates from the air and terrestrial sources to the marine environment [ 102 ], and was detected in feedstuffs, such as meat-bone meal and fish meal from aquaculture [ 103 ], and in molluscs and fish collected from the Southern Baltic Sea [ 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thorium has three alpha-emitting radioisotopes: 228Th (T 1/2 = 1.91 y), 230Th (T 1/2 = 7.54 × 10 4 y), 232 Th (T 1/2 = 1.4 × 10 10 y) [ 99 ], has very low water solubility and strongly adsorb onto organic/inorganic particles, being therefore rather unavailable for biological uptakes [ 100 ]. Adsorbed Th enters the human body through inhalation or ingestion or through skin wounds and excessive exposure can induce cancer of the liver, lungs, pancreas, spleen, bone, and blood [ 101 ]. Th originates from the air and terrestrial sources to the marine environment [ 102 ], and was detected in feedstuffs, such as meat-bone meal and fish meal from aquaculture [ 103 ], and in molluscs and fish collected from the Southern Baltic Sea [ 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…A test evaluating the toxic effects of each nanoclay type on algal population growth revealed that Cloisite 30B was more toxic than the other 2 nanoclay types (Results ‐ Chlamydomonas reinhardtii ), and results from our elemental analysis (Results ‐ Elemental composition of nanoclays) indicate that Cloisite 30B has higher amounts of fluorine (F) and thorium (Th), both of which are known to be harmful to algae (Smith and Woodson ; Hekman et al ; Peng et al ). We evaluated the degree to which each of the nanoclays we studied leached F and Th into solution.…”
Section: Methodsmentioning
confidence: 90%
“…Fluorine is a very strong oxidizing agent and can negatively affect the population growth of algae when its concentration exceeds 10 mg/L (Smith and Woodson ; Hekman et al ; LeBlanc ; Joy and Balakrishnan ; Bhatnagar and Bhatnagar ; Camargo ). Thorium has a high affinity for living material in aquatic environments (Gadd and White ) and can inhibit the population growth of the green algae Chlorella pyrenoidosa when the concentration exceeds 7.2 μM (Peng et al ). We found that Cloisite 30B releases very low concentrations of F (x¯ ± 1 SD = 0.02 ± 0.003 mg /L) and Th (nondetectable levels) into water.…”
Section: Discussionmentioning
confidence: 99%
“…Algaes are an important component of the marine ecosystem. Algaes are ubiquitous in the water system and have colonized almost every part of the globe [2]. Since ancient times, they have been used for food, feed, fertilizer, and medicine all over the world, and they are still used in skin care products today.…”
Section: Introductionmentioning
confidence: 99%